Pejotization: transformation of employees into legal entity - Junior, Romeu Felix Menin (Revista Coleta Científica, 2019)
The theme of this article is pejotização: Transforming the employee into a legal entity. He investigated the following problem: Pejotizar is to hire legal entities instead of natural persons through an autonomous service contract, does the worker end up being harmed? The objective of this work is: To identify and analyze what are the practical consequences for the worker's life, evaluating the legal limits of such an institute and its consequences when used for purposes of removing the incidence of labor legislation. This work is important for an operator of the Law, because it addresses the reflexes in the worker's life, evaluating the legal limits of such institute and its consequences when used for purposes of removing the incidence of labor legislation. This is a qualitative theoretical research lasting six months. It is concluded that this is a type of employment contract, which in the irregular version, besides constituting labor and social security fraud, constitutes a precarious type of work that does not present substantial gains for either side and, for these reasons, must be avoided.